2005
DOI: 10.1536/ihj.46.845
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Heart Rate Recovery in Patients With Heart Failure Effect of Fluvastatin Therapy

Abstract: SUMMARYHeart rate recovery is the difference in heart rate at peak exercise and at a specific time interval following the onset of recovery. Attenuated heart rate recovery is an independent predictor of mortality in patients with a history of coronary artery disease. The aim of the present study was to evaluate the effect of a statin on heart rate recovery, particularly in patients with ischemic heart failure and hyperlipidemia. Twenty-nine consecutive hyperlipidemic, stable coronary artery disease patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
1
5
0
1
Order By: Relevance
“…Heart rate recovery (HRR) was calculated as the difference between heart rate at peak exercise and heart rate at the relevant minute of recovery. Exercise test findings of this population were reported earlier [12].…”
Section: Exercise Testingsupporting
confidence: 73%
See 1 more Smart Citation
“…Heart rate recovery (HRR) was calculated as the difference between heart rate at peak exercise and heart rate at the relevant minute of recovery. Exercise test findings of this population were reported earlier [12].…”
Section: Exercise Testingsupporting
confidence: 73%
“…In this context, 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors, statins, were propounded in HF by their ability to downregulate inflammatory cytokines [6][7][8], improve endothelial function [9], reverse myocardial remodeling [10], and provide salutary neural effects [11,12]. The effects of these agents to improve clinical outcomes in HF patients, however, remain controversial [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that medical treatment with different agents (e.g. beta blockers, statins) might affect HRR 33 . Treatment of patients with metabolic syndrome via beta blockers, statins, and weight reduction via diet, exercise and pharmacological anti‐obesity agents may ensure improvement in autonomic functions which may be determined with HRR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of this finding is unknown in so far as there is an inverse relationship between MSNA and LF spectral power as heart failure progresses [108], and in a multivariate analysis involving heart failure patients reduced daytime LF power of HR was an independent predictor of increased risk of sudden cardiac death [109]. In a controlled study, 3 months of fluvastatin (80 mg/day) reduced total cholesterol and LDL-cholesterol, and increased HR recovery at 1 and 3 min following a maximal exercise test in 29 hyperlipidaemic patients with ischaemic cardiomyopathy (LVEF <40 %) [110].…”
Section: Chronic Heart Failurementioning
confidence: 98%